Comprehensive insights from composition to functional microbe-based biodiversity of the infant human gut microbiota - Gabriele Andrea Lugli; Leonardo Mancabelli; Christian Milani; Federico Fontana; Chiara Tarracchini; Giulia Alessandri; Douwe van Sinderen; Francesca Turroni; Marco Ventura (npj Biofilms and Microbiomes, 2023)
Abstract During infancy, gut microbiota development is a crucial process involved in the establishment of microbe–host interactions which may persist throughout adulthood, and which are believed to influence host health. To fully understand the complexities of such interactions, it is essential to assess gut microbiota diversity of newborns and its associated microbial dynamics and relationships pertaining to health and disease. To explore microbial biodiversity during the first 3 years of human life, 10,935 shotgun metagenomic datasets were taxonomically and functionally classified. Microbial species distribution between infants revealed the presence of eight major Infant Community State Types (ICSTs), being dominated by 17 bacterial taxa, whose distribution was shown to correspond to the geographical origin and infant health status. In total, 2390 chromosomal sequences of the predominant taxa were reconstructed from metagenomic data and used in combination with 44,987 publicly available genomes to trace the distribution of microbial Population Subspecies (PS) within the different infant groups, revealing patterns of multistrain coexistence among ICSTs. Finally, implementation of a metagenomic- and metatranscriptomic-based metabolic profiling highlighted different enzymatic expression patterns of the gut microbiota that allowed us to acquire insights into mechanistic aspects of health-gut microbiota interplay in newborns. Comparison between metagenomic and metatranscriptomic data highlights how a complex environment like the human gut must be investigated by employing both sequencing methodologies and possibly supplemented with metabolomics approaches. While metagenomic analyses are very useful for microbial classification aimed at unveiling key players driving microbiota balances, using these data to explain functionalities of the microbiota is not always warranted.